Pengaruh Kualitas Pelayanan, Fasilitas, dan Harga terhadap Kepuasan Pelanggan (Studi Kasus di Lembaga Bimbingan Belajar Sukses Jakarta) - Suhardi, Yusuf; Burda, Agustian; Darmawan, Arya; Zulkarnaini, Zulkarnaini; Fidayanti, Fidayanti (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
This research aims to determine the influence of service quality, facilities and prices on customer satisfaction at the Jakarta Success Education Institute.The strategy used is an associative strategy. The research method used in this research is a survey method, using a questionnaire as a data collection tool. The respondents sampled in this research were 134 consumers at the Success Education Institute. The analysis tool used is SPSS.The research results show that partially there is a significant influence on service quality, facilities and prices on customer satisfaction at PT. Jakarta Success Education.